Complete bladder eversion in periparturient Nellore cow – case report - Silva, J. R.B. [UNESP]; Baumam, C. A.E. [UNESP]; Mendonça, A. P.A. [UNESP]; Ferreira, J. C.P. [UNESP]; Hussni, C. A. [UNESP]; Alves, A. L.G. [UNESP]; Watanabe, M. J. [UNESP]; Rodrigues, C. A. [UNESP] (FapUNIFESP (SciELO), 2023)
Partial or complete bladder eversion is a rare condition of poor prognosis in cows, commonly associated with intense tenesmus observed in the peripartum period. A 14-year-old obese Nellore cow at 280 days of gestation was referred with 24-hour bladder prolapse. The bladder was complete eversion through the vulvar vestibule showing a thick congested wall and small residual urine volume. After clinical examination, the cow received scopolamine butylbromide and intercoccygeal epidural anesthesia, and the externalized bladder segment was partially reduced, remaining only 10 cm externalized. The cow was maintained with an intravesical human gastric tube number 16 and constant monitoring. The eversion was fully reduced after 12 hours of local treatment, and as the cow presented subclinical ketosis, hypocalcemia and cystitis, antibiotic, glucose, calcium and propylene glycol therapy were performed. We opted for induction of parturition, and after 24 hours, a healthy 52kg calf was born and the placenta was delivered 16 hours after calving. The cow and calf were discharged on the sixth day of hospitalization, with no recurrences or secondary complications after treatment.
Eversão completa de bexiga no pré-parto em vaca Nelore – relato de caso
Keywords: cattle; cystitis; everted bladder; pregnant cow